Monetary and Financial Statistics Manual. (Manuals and Guides; MG, 2000)
This Manual offers guidelines for the presentation of monetary and financial statistics. It provides a set of tools for identifying, classifying, and recording stocks and flows of financial assets and liabilities, describes the standard, analytically oriented frame works in which the statistics may be presented, and identifies a set of analytically useful aggregates within those frameworks. The concepts and principles set out in the Manual are harmonized with those of the System of National Accounts 1993.